Surprise, surprise! High-tech is still where the action is! - Thompson, Garland L. (Crisis (00111422), 1993)
Reports on several developments reflecting the dominance of high-technology businesses in the United States. Team up of AT&T with telecommunications companies in Europe and Asia; Alliance between MCI and British Telecommunications; Efforts of cable television companies to enter into personal communications network.